Analisis Syahadat sebagai Ujaran Performatif dalam Speech Act Theory John L. Austin - Nayaka Inabhimantra Wiwudha; Syauqi Royyan Fa'izul Khak; Muhammad Nikmal Anas Alhadi; Ika Yunia Fauzia (Media: Jurnal Filsafat dan Teologi, 2026)
This study analyzes the shahada through the framework of speech act theory developed by John Langshaw Austin. Traditionally, the shahada has been interpreted within a normative theological framework as a declaration of faith and the foundation of Muslim identity. This research aims to broaden that understanding by examining the shahada as a performative utterance that carries linguistic action and social implications. The study employs a qualitative approach based on library research and conceptual analysis of Austin’s speech act theory and its systematic development by John Searle. The findings demonstrate that the recitation of the shahada can be understood as a performative act involving locutionary, illocutionary, and perlocutionary dimensions simultaneously. Within the social context, the shahada functions as a linguistic declaration that marks an individual’s transition into the Muslim community. However, the analysis also reveals  the limitation of speech act theory in addressing the ontological and existential-transcendent dimension of the shahada, since Austin’s performativity primarily relies on social conventions rather than theological realities that transcend linguistic structures.